The Human–Animal Relationship as the Focus of Animal-Assisted Interventions: A One Health Approach - Menna, Lucia Francesca; Santaniello, Antonio; Todisco, Margherita; Amato, Alessia; Borrelli, Luca; Scandurra, Cristiano; Fioretti, Alessandro (International journal of environmental research and public health, 2019)
Background: Animal-assisted intervention (AAIs) represent an adequate expression of integrated medicine, according to the One Health approach. We argue that AAIs are interventions based on interspecific relationships between humans and animals. Although there are many studies on the effects of AAIs on animal and human health and wellbeing, research is still needed to give us more data. For example, information is still lacking on the aspects characterizing and influencing the interspecific relationships occurring in AAIs. The efficacy of an intervention based on interspecific relationships will be influenced by different factors, such as attachment styles and personalities of both the animal and the handler, an appropriate choice of animal species and their individuality, animal educational training techniques, the relationship between the handler and the animal, and relational reciprocity between animal, the patients, and members of the working team. Method: This article aims to contribute to the study of interspecific relationships in AAIs via theoretical considerations. An interspecific relationship determines the result of safe interventions, which directly influences the welfare of the animal. Results and considerations: AAIs should be evaluated systemically as a network within a process in which every component interacts with and influences other components. Standardized methods using appropriate tests and parameters are needed to better select appropriate animals (i.e., species and individual subjects) using interspecific relational competences as well as appropriate educational training methods and health protocols to assess potential risks.